2021
DOI: 10.1016/j.redox.2021.102033
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of TXNIP-mediated oxidative stress and NLRP3 inflammasome activation contributes to SAHH inhibition-aggravated diabetic nephropathy

Abstract: S-adenosylhomocysteine (SAH) is hydrolyzed by SAH hydrolase (SAHH) to homocysteine and adenosine. Increased plasma SAH levels were associated with disturbed renal function in patients with diabetes. However, the role and mechanism of SAHH in diabetic nephropathy is still unknown. In the present study, we found that inhibition of SAHH by using its inhibitor adenosine dialdehyde (ADA) accumulates intracellular or plasma SAH levels and increases high glucose-induced podocyte injury and aggravates STZ-induced diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 54 publications
3
52
0
Order By: Relevance
“…One is the activation of the NF-κb pathway which promotes the synthesis of NLRP3 protein and IL-1β precursor protein, the other is to trigger the assembly of the inflammasome, such as the production of ROS or TXNIP [ 18 ]. TXNIP is a key regulatory protein that boosts oxidative stress and has recently been identified as an NLRP3 binding protein that activates the NLRP3 inflammasome [ 50 , 51 ]. Our previous investigation, by co-immunoprecipitation, disclosed that TXNIP engages in NLRP3 activation after CVST [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…One is the activation of the NF-κb pathway which promotes the synthesis of NLRP3 protein and IL-1β precursor protein, the other is to trigger the assembly of the inflammasome, such as the production of ROS or TXNIP [ 18 ]. TXNIP is a key regulatory protein that boosts oxidative stress and has recently been identified as an NLRP3 binding protein that activates the NLRP3 inflammasome [ 50 , 51 ]. Our previous investigation, by co-immunoprecipitation, disclosed that TXNIP engages in NLRP3 activation after CVST [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…TXNIP is a regulator of oxidative stress [13] and has been studied in many diseases such as pancreatic cancer [12,36], but how ERS regulates oxidative stress in AP is still unknown. A previous study demonstrated that TXNIP is regulated by p-IRE1α in hepatocytes [37].…”
Section: Discussionmentioning
confidence: 99%
“…TXNIP inhibits the antioxidant activity of thioredoxin by binding to the protein [7]. TXNIP has been widely studied in other diseases, for example, Bechard et al found that TXNIP improved pancreatic cancer due to the inhibition of metastasis [12], Zhang et al found that TXNIP alleviated diabetes by exacerbating oxidative stress [13]. In addition, TXNIP is related to reactive oxygen species (ROS) bursts in cells.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, inflammation is an important bridge to podocyte injury studies. It often mediates podocyte injury together with autophagy and oxidative stress ( Hou Y. et al, 2020 ; Dai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%